An analytical expression for ion velocities at the wall including the sheath electric field and surface biasing for erosion modeling at JET ILW. (August 2017) - Borodkina, I.; Borodin, D.; Brezinsek, S.; Kirschner, A.; Tsvetkov, I.V.; Kurnaev, V.A.; Bobkov, V.; Klepper, C.C.; Lasa, A.; Guillemaut, C.; Jacquet, P.; Stamp, M.F.; et al.
Highlights: An analytical expression for the ion velocity just before the surface impact including the local electric field and an optional surface biasing effect is presented for simulation of plasma-facing components' erosion in fusion experiments. Energy and angular impact distributions and the resulting effective sputtering yields were produced for several experimental scenarios at JET ILW mostly involving PFCs exposed to an oblique magnetic field. The analytic solution has been applied as an improvement to earlier ERO modeling of localized, Be outer limiter, RF-enhanced erosion, modulated by toggling of a remote, magnetically connected ICRH antenna. The effective W sputtering yields due to D and Be ion impact in Type-I and Type-III ELMs and inter-ELM conditions were estimated using the analytical approach and benchmarked by spectroscopy. Abstract: For simulation of plasma-facing component erosion in fusion experiments, an analytical expression for the ion velocity just before the surface impact including the local electric field and an optional surface biasing effect is suggested. Energy and angular impact distributions and the resulting effective sputtering yields were produced for several experimental scenarios at JET ILW mostly involving PFCs exposed to an oblique magnetic field. The analytic solution has been applied as an improvement to earlier ERO modelling of localized, Be outer limiter, RF-enhanced erosion, modulated by toggling of a remote, however magnetically connected ICRH antenna. The effective W sputtering yields due to D and Be ion impact in Type-I and Type-III ELMs and inter-ELM conditions were also estimated using the analytical approach and benchmarked by spectroscopy. The intra-ELM W sputtering flux increases almost 10 times in comparison to the inter-ELM flux.